PENGARUH GAYA KEPEMIMPINAN, SUPERVISI KERJA DAN DISIPLIN KERJA TERHADAP EFEKTIFITAS GURU DI SMA NEGERI 2 KOTAPINANG LABUHANBATU SELATAN - Meisa Fitri Nasution (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to analyze the effect of leadership style, work supervision and work discipline on work effectiveness. The population is 34 employees of SMA Negeri 2 Kotapinang Labuhanbatu Selatan. The analysis used is multiple linear regression analysis with the help of SPSS 20.00 for Windows. The results of this study indicate that leadership style, work supervision and work discipline have a positive and significant effect on the work effectiveness of teachers at SMA Negeri 2 Kotapinang Labuhanbatu Selatan. This can be seen from the R Square value of 0.715 or 71.5%, the remaining 28.5% can be explained by other variables not included in this research model.